Painless labour: attitude and awareness amongst pregnant women - Sinha, Archana; Abhilashi, Kavya; ., Snehkiran; Prasad, Dipali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Labour pain has been described as most severe pain experienced by a female. Labour analgesia is widely practiced in developed countries. Many labour analgesic methods have been introduced to make delivery a pleasurable moment in a women’s life. Methods: This prospective study was performed at the Department of Obstetrics and Gynaecology, Indira Gandhi Institute of Medical Sciences, Patna, India after getting permission from institute ethical committee. 100 pregnant females attending the antenatal clinic were interviewed in their mother language. Information was collected on a questionnaire after an informed consent. The aim of the study was to assess the knowledge, desire and acceptability of pregnant women regarding painless labour. Results: The mean age of the women in the study was 24.98years.56% of women in the study were primigravida whereas 44% were multigravida.66% women belonged to urban area while 34% were from rural area. 10% were illiterate, 35% were educated upto secondary education and 55% were having higher education. Only 24% of the women were having knowledge about painless labour however 87% female were having positive attitude towards epidural analgesia. The correlation between the educational status and knowledge about painless labour was not statistically significant (p0.949). The knowledge and attitude of women regarding painless labour was statistically significant with p value of 0.00001. Conclusions: There is lack of knowledge about labour analgesia among women. Obstetrician and anaesthetist should educate women regarding painless labour. Labour analgesia is standard of care in obstetrics and should be provided to all parturient.